Emotional, coping factors and personality traits that influenced alcohol consumption in Romanian students during the COVID-19 pandemic. A cross-sectional study - Cornelia Rada; Cristina Faludi; Mihaela Lungu (BMC Public Health, 2024)
Abstract Background During the COVID-19 pandemic, after 3 months from the installation of the state of emergency on the territory of Romania, data were collected from 677 students and master’s students, to explore the problematic alcohol consumption (AC). Methods The evaluation was done with: Alcohol Use Disorders Identification Test, Depression, Anxiety and Stress Scales, Strategic Coping Approach Scale and The Freiburg Personality Inventory. The statistical methods used were linear regression with bootstrap procedure, Spearman’s rank correlation, and the Mann-Whitney U test. Results More than half were affected by depression or anxiety of moderate to extremely severe intensity. The prevalence of problematic alcohol consumption was low: (Hazardous and Extremely Hazardous (2.3) and Medium Risk (10.2). Early onset increases the subsequent risk of problematic AC, compared to women, men recorded a higher AC (p <.01). Anxiety, antisocial action, personality traits Aggressiveness and Somatic complaints had the effect of increasing the alcohol consumption score (p <.01). Significant but weak positive correlations between AC on one hand, and depression, anxiety, stress and antisocial action on the other hand were found (p <.01). Conclusions Probably the prevalence of AC was low as a result of the fact that most respondents were studying in the field of health promotion and as a result of the closure of entertainment venues. This study advocates for the education of youngsters to clearly express their opinions without violating the boundaries of others’ feelings (assertive action) and to act prudently in dangerous or uncertain situations (cautious action) since these coping mechanisms were not associated with problematic alcohol consumption. The promotion of positive, achievement-oriented, life attitudes is equally important, as these characteristics of the Life Satisfaction personality dimensions were also found as non-determinants of alcohol-induced problems. The association of problematic AC with antisocial actions as a coping mechanism and high scores on Aggressiveness calls for interventions to educate the younger generation how to acquire and adopt healthy mechanisms to control tensions without resorting to alcohol consumption, more so as the two variables reinforce each other. Drinking as a means of gaining courage must be carefully reconsidered since anxiety generally hits back, often in increased levels.